3(5x+9)=37+19

Simple and best practice solution for 3(5x+9)=37+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+9)=37+19 equation:


Simplifying
3(5x + 9) = 37 + 19

Reorder the terms:
3(9 + 5x) = 37 + 19
(9 * 3 + 5x * 3) = 37 + 19
(27 + 15x) = 37 + 19

Combine like terms: 37 + 19 = 56
27 + 15x = 56

Solving
27 + 15x = 56

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 15x = 56 + -27

Combine like terms: 27 + -27 = 0
0 + 15x = 56 + -27
15x = 56 + -27

Combine like terms: 56 + -27 = 29
15x = 29

Divide each side by '15'.
x = 1.933333333

Simplifying
x = 1.933333333

See similar equations:

| x^2-27y^2=12 | | A^2+12a=-32 | | -3=p/6-6 | | 8a+-3=5 | | 3(2x+3)=2x-7 | | 7(4x-6)-7=28x-49 | | ln(x+2)+ln(x+4)=2 | | 3x+5x-4=4 | | 4(5x+6)+2(8-x)= | | 8y+3y+18=2y | | P^2=35+2p | | 106.2+4x=180 | | 11y-6=2y | | -.5*32x^2+24x+50=58 | | -3+5y=17 | | 28.5+.75x=36.75 | | (7xa)x(a-a)-7=56 | | 7(7x-4)+11x= | | 9-74r-7= | | 2m^2+4m-30=0 | | 2(3x+1)+5x(x-2)= | | A^2=a+20 | | 2x^2-15x+35=0 | | 6x+2+2-10= | | -51-5x=75-12x | | 6x+5+5x+3+8x+1=180 | | 19x=41 | | 14=6n+10 | | -(2x-3+4y)= | | -1/5(x-15)-1/9(x-9)=x-3 | | 24x-48=3x^2 | | N^3-4n=32 |

Equations solver categories